PENGARUH KUALITAS SUMBER DAYA MANUSIA DAN KOMITMEN ORGANISASI TERHADAP PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL DENGAN PEMANFAATAN SISTEM INFORMASI AKUNTANSI SEBAGAI VARIABEL MODERASI - I Putu Ari Sutrisna; Sang Ayu Putu Arie Indraswarawati; Cokorda Gede Bayu Putra (UNHI Press, 2021)
This study aims to determine the Effect of Quality of Human Resources and Organizational Commitment on the Implementation of Accrual Based Government Accounting Standards with the Utilization of Accounting Information Systems as Moderation Variables in the Financial Management Agency and Regional Assets of Gianyar Regency. The sample used in this study was the BPKAD office in Gianyar Regency who worked in accounting and finance. The sampling technique is done by using a questionnaire with a total sample of 40 respondents. Data analysis using Multiple Linear Regression Analysis. The results of this study indicate that the HR variable has a positive effect, the organizational commitment variable has a positive effect, the variable utilization of the Accounting Information System has a positiveeffect on the application of accrual-based government accounting standards.